1997
DOI: 10.1016/s0092-8674(00)80530-9
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Polarizes an Early C. elegans Blastomere to Distinguish Endoderm from Mesoderm

Abstract: A polarizing signal induces endoderm production by a 4-cell stage blastomere in C. elegans called EMS. We identified 16 mutations in five genes, mom-1 through mom-5, required for EMS to produce endoderm. mom-1, mom-2, and mom-3 are required in the signaling cell, P2, while mom-4 is required in EMS. P2 signaling downregulates an HMG domain protein, POP-1, in one EMS daughter. The sequence of mom-2 predicts that it encodes a member of the Wnt family of secreted glycoproteins, which in other systems activate HMG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
504
1
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 468 publications
(533 citation statements)
references
References 43 publications
27
504
1
1
Order By: Relevance
“…Genetic epistasis analyses demonstrated that porcupine acts upstream of intracellular signaling components in a cell non-autonomous manner (van den Heuvel et al, 1993;Noordermeer et al, 1994;Siegfried et al, 1994;Manoukian et al, 1995;Tanaka et al, 2000). In addition, a genetic screen for maternally expressed genes required for the endoderm induction in Caenorhabditis elegans confirmed the cell non-autonomous role of mom-1 (C. elegans porcupine ortholog) in Wnt signaling (Thorpe et al, 1997).…”
Section: Porcupine Lipid Modifies Wntsmentioning
confidence: 97%
See 1 more Smart Citation
“…Genetic epistasis analyses demonstrated that porcupine acts upstream of intracellular signaling components in a cell non-autonomous manner (van den Heuvel et al, 1993;Noordermeer et al, 1994;Siegfried et al, 1994;Manoukian et al, 1995;Tanaka et al, 2000). In addition, a genetic screen for maternally expressed genes required for the endoderm induction in Caenorhabditis elegans confirmed the cell non-autonomous role of mom-1 (C. elegans porcupine ortholog) in Wnt signaling (Thorpe et al, 1997).…”
Section: Porcupine Lipid Modifies Wntsmentioning
confidence: 97%
“…Furthermore, it is exciting to consider that Wls/Evi/ Mom-3 had previously been discovered in a genetic screen in C. elegans (Thorpe et al, 1997) and was only recently identified molecularly, opening the door to the possibility that other as yet unknown pathway components are waiting to be uncovered.…”
Section: Wnt Secretionmentioning
confidence: 99%
“…In the absence of Wnt signaling, the centrosome does not move and PLM polarity is inverted relative to wild type. Wnt signaling via GSK-3 can induce centrosome movement and reorient the mitotic spindle in the C. elegans early embryo independently of gene transcription (Rocheleau et al, 1997;Thorpe et al, 1997;Schlesinger et al, 1999). Similarly, the ALM/BDU precursor divides along the AP body axis to produce the anterior daughter ALM and posterior daughter BDU.…”
Section: Model For Plm Polarity Regulation By Lin-44mentioning
confidence: 99%
“…elegans has five Wnts [CWN-1, CWN-2, EGL-20, LIN-44 and MOM-2 (Shackleford et al, 1993;Herman et al, 1995;Thorpe et al, 1997;Whangbo and Kenyon, 1999)], four Frizzleds [CFZ-2, LIN-17, MIG-1 and MOM-5 (Sawa et al, 1996;Rocheleau et al, 1997;Zinovyeva and Forrester, 2005;Pan et al, 2006)] and a single Ryk, LIN-18 (Inoue et al, 2004). Wnt signaling establishes the polarity of asymmetric cell divisions, determines cell fates and guides cell migrations (Korswagen, 2002;Herman, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation